La Sindrome delle Apnee Ostruttive del Sonno (OSAS) e i disturbi dell’umore in una popolazione di autotrasportatori / Obstructive Sleep Apnoea Syndrome and mood disorders in a population of public transport drivers - Ruberto, M.; Liotti, F. (La Medicina del Lavoro, 2011)
«Obstructive Sleep Apnoea Syndrome (OSAS) and mood disorders in a population of public transport drivers». Background: A growing number of reports pinpoint the high prevalence of mood disorders in OSAS patients. The aim of the study was to verify the presence of depressive mood disorders and their relationship with OSAS in a population of public transport drivers. Methods: 164 city bus drivers underwent an anthropometric and biochemical assessment, administration of ESS and Zung Scale questionnaires and cardio-respiratory polysomnography (PSG). The data were compared with a matched control group of 171 subjects. Results: The two groups of subjects differed as regards BMI (p<0.001), neck circumference (p<0.001), fasting plasma glucose (p<0.001), basal insulin (p<0.001) and HOMA index (p<0.001), degree of daytime sleepiness (p<0.001) and Zung scale score (p<0.001). PSG revealed significant differences in AHI (p<0001), ODI (p<0001), in the absolute and mean values of the nadir of the ODI (for both p<0001), in total sleep time with O2 saturation level values <90% (p<0.001) and <80% (p<0.001). Pearson’s correlation analysis showed a linear relationship between AHI and Zung scale (r=0.75, p=0.000) and between ODI and ESS (r=0.59, p=0.000). Conclusions: The role of sleep-related breathing disorders in mood modulation is well known from the literature. Our results highlight the relationship between OSAS and mood lowering in urban bus drivers, suggesting the need for a multidisciplinary approach to assess the health of this occupational group, including assessment of any sleep disorders, with particular reference to those of a respiratory nature.